68 "Registrar ready" – a pilot study day simulating a night shift to develop departmental management skills for emergency medicine trainees transitioning on the middle grade and senior rotas. (17th November 2016) - Williamson, Katherine; Platt, A; Hurley, J; Stock, N; Hunter, I
Abstract : The College of Emergency Medicine (2014) has highlighted that non-technical skills have a vital role to play in Emergency Medicine practice both to help reduce human error and enhance risk management in order to improve patient care and safety. Over recent years the demand on Emergency Departments has continued to increase. Trainers have recognised that the transition from junior positions to a middle grade role is extremely stressful. A survey was undertaken of all CT2 and CT3 in the region regarding their concerns and previous trainee experience of this transition, in addition to collating a list of common difficulties for new registrars as perceived by senior staff nurses in Emergency Medicine in this region. The study day revolves around of a table top exercise with breakout simulation scenarios. The board represents the layout of an emergency department and a faculty member feeds patient cards into the department in real time. Several simulation scenarios branch out from the exercise room with multiple scenarios involving mannequins, simulated patients and role players running parallel in a ward based surrounding. The day is divided into six sections representing a time-lapse of a twelve hour nightshift. Each of the scenarios and evolving challenges presented to the participants reflect one or more specific concerns identified by the trainees from the survey. After each segment, the debrief addresses any specific issues raised and the experienced faculty provide guidance as to a method to approach them. Feedback was collated from both faculty and participants with high Likert score means for coverage of management topics and 100% strongly agreement that the day met its objectives to ease transition into first middle grade posts. Higher level trainees involved as faculty commented that they would have appreciated such a training experience prior to starting their higher training posts.